Immunogenicity of COVID-19 vaccines in patients with cirrhosis: A meta-analysis - Lichen Ouyang; Gang Lei; Yeli Gong (Human Vaccines & Immunotherapeutics)
The immunogenicity of COVID-19 vaccines in patients with liver cirrhosis remains largely unknown. The purpose of this meta-analysis was to investigate the immunogenicity of COVID-19 vaccines in patients with cirrhosis and compare the humoral and cellular immune responses following complete COVID-19 vaccination between cirrhosis patients and healthy controls. A systematic literature search was conducted in PubMed, EMBASE, and Web of Science from 1 January 2020 to 22 August 2023. Sixteen studies with 2127 cirrhosis patients were included. The pooled seroconversion rate in patients with cirrhosis following complete COVID-19 vaccination was 92.4% (95% CI, 86.2%–96%, I2 = 90%) with significant between-study heterogeneity. Moreover, COVID-19 vaccination elicited a higher humoral immune response in patients of compensated cirrhosis as compared with decompensated cirrhosis (RR = 1.069, 95% CI, 1.011–1.131, I2 = 17%, p = .019). Additionally, 10 studies were included for comparison analysis of seroconversion rate between cirrhosis patients and healthy controls. The results showed that the seroconversion rate in patients with cirrhosis was slightly lower compared with healthy controls (RR = 0.972, 95% CI, 0.955–0.989, I2 = 66%, p = .001). Meanwhile, the pooled RR of cellular immune response rate for cirrhosis patients vs. healthy controls was 0.678 (95% CI, 0.563–0.817, I2 = 0, p < .0001). Our meta-analysis demonstrated that COVID-19 vaccination elicited diminished humoral and cellular immune responses in patients of cirrhosis. Patients with cirrhosis particularly decompensated cirrhosis who have completed full-doses of COVID-19 vaccination should receive continuous attention and preemptive measures.